Fluid motion and shear forces in platelet storage bags with different modes of agitation. Issue 2 (14th April 2016) - Torres, Richard; Tormey, Christopher A.; Stack, Gary
Abstract : This study describes a new method for comparison of fluid motion and associated shear forces with various modes of platelet agitation. Fluid motion generated by flatbed, tumbler‐type and circular platelet agitators was investigated. Trajectory tracings of polyethylene beads suspended inside platelet storage bags were used to calculate motion parameters. Mean particle speeds generated by flatbed agitation were approximately 25‐fold greater than those generated by 3‐rpm tumbler‐type agitation, corresponding to a wall shear stress increase in approximately sevenfold for flatbed agitation. As such, flatbed agitation is more likely to contribute to shear‐associated changes in platelets than other modes of agitation.